2023
DOI: 10.1039/d2ee03413a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of oxygen evolution activity by tuning e*g band broadening in nickel oxyhydroxide

Abstract: Nickel oxyhydroxides (NiOOH) derived from the reconstruction of Ni-based pre-catalysts are the active species for oxygen evolution reaction (OER). Although chemically similar, these NiOOH exhibited differentiated OER activities that show...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 46 publications
1
67
0
Order By: Relevance
“…Recently, we thoroughly analyzed the structure difference of reconstructionderived X-Ni(OH) 2 (X = NiS 2 , NiSe 2 , and Ni 5 P 4 ). [16] FT-EXAFS showed that the fitted Ni-O bond distances were 2.03916 Å, . This result proved that a higher extent of strain would lead to the stronger e g * band broadening around the Fermi level.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 96%
“…Recently, we thoroughly analyzed the structure difference of reconstructionderived X-Ni(OH) 2 (X = NiS 2 , NiSe 2 , and Ni 5 P 4 ). [16] FT-EXAFS showed that the fitted Ni-O bond distances were 2.03916 Å, . This result proved that a higher extent of strain would lead to the stronger e g * band broadening around the Fermi level.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 96%
“…Recently, Zhong et al also noticed this phenomenon in typical Ni-based pre-catalysts, including NiS 2 , NiSe 2 , and Ni 5 P 4 , which exhibit differentiated oxygen evolution activities. 111 For NiS 2 , NiSe 2 , and Ni 5 P 4 , different extents of strain were observed in these reconstructed NiOOH. A stronger strain leads to a greater NiO 6 octahedron distortion in NiOOH, which broadens the e g band and thus enhances the catalytic performance.…”
Section: Surface Engineeringmentioning
confidence: 86%
“…In addition, the weakening of the peak area of the S–O bond and the shifts of S 2p 1/2 and S 2p 3/2 (Figure f) are closely related to the oxidation of the metal species during the catalytic process. In common, metal sulfides prefer to undergo structural reconfiguration during OER, forming hydroxides. The Raman spectrum of FeOOH/Co 9 S 8 /Ni 3 S 2 after the OER test further confirmed the existence of the hydroxide layer. For the activated FeOOH/Co 9 S 8 /Ni 3 S 2 electrode, the Raman band at 486 cm –1 is attributed to the CoOOH stretching vibration, while the band at 548 cm –1 is assigned to NiOOH (Figure S14).…”
mentioning
confidence: 85%